Design and implementation of voltage regulator for a power supply - Aung, Kyaw Htet (Nanyang Technological University, 2022)
Voltage regulators are essential in every power supply module to provide stable supply. Their main purpose is acting as medium to withstand varying input while providing regulated output. In modern electronics era, regulating topologies, methods, and techniques are evolving to be more intelligent, smart, and energy efficient. A good regulator should keep target workload to function properly without sacrificing its power rating. In this project, various regulators ranging from simple integrated circuits (ICs) to complex adjustable switching regulator are learned, implemented, and tested. It illustrates a full learning process including software simulation, programming, troubleshooting, problem solving and prototyping. Two majority type of regulators, linear and switching regulators are studied in this project. In linear category, L7805 ICs are learned as 5V linear regulator. Ćuk Converter, Single ended primary inductor converter (SEPIC) as buck converter, and MC34063AB ICs in switching category are simulated in both buck and boost configurations. All circuit simulations are exercised through NI Multisim, and Proteus software. NI Ultiboard is used to design PCB circuit design. Input waveform to drive switching topologies are gained from Arduino IDE software. Hence, this final year project consists of several learning activities from software simulation, programming to hardware prototyping such as soldering and components assembly through breadboard and printed circuit boards PCB.